A Case of Atypical Mucin Balls Wearing Extended Wear of Silicone Hydrogel Lens for Therapeutic Use. (27th April 2013) - Matsuzaki, Yusuke; Toshida, Hiroshi; Ohta, Toshihiko; Murakami, Akira
Abstract : A 25-year-old man visited our hospital showing atopic conjunctivitis and corneal shield ulcer on his left eye. Although eye drops of 0.1% of betamethasone sodium phosphate and 0.1% of hyaluronic acid ophthalmic solution were prescribed, calcific corneal opacities developed. The corrected visual acuity decreased to 6/20 in Snellen chart. After corneal epithelial exfoliation, removal of calcific corneal opacity was scrubbed with MQA soaked in 0.05 M of ethylenediaminetetraacetic acid (EDTA). After washing the eye with 200 mL of physiological saline, a silicon hydrogel lens, PureVision (balafilcon A), was inserted to obtain pain relief for the therapeutic use. At postoperative day 11, mucin balls were found between cornea and contact lens and stained by rose bengal dye. One of them was atypically larger than usual, and the major axis was approximately 1.5 mm. Wearing lens was stopped, and all of mucin balls and corneal staining were disappeared at postoperative day. Little corneal opacity remained, and visual acuity after surgery recovered to 14/20 at five months.